The Golden Age of Southern Cameroons: Prime Lessons for Cameroon. - Ndi, Anthony (African Books Collective : Spears Media Press, 2016)
This book argues that since the emergence of the Cameroon National Union (CNU) and the one-party state in 1966, Cameroonians have progressively degenerated into the syndrome of collective amnesia inspired by a culture of sycophancy, glorifying and deifying political leadership. These developments stand in stark contrast to what obtained in the nascent Southern Cameroons - the UN Trust territory administered by Britain until 1961 when its population voted overwhelmingly by 70.5% to gain their independence by establishing a federation with the then French-speaking Republic of Cameroon. From the late 1950s until the dismantling of the Cameroon Federation, Southern Cameroons and later West Cameroon had a vibrant parliament, a House of Chiefs (or Senate), an independent Judiciary, an ideal, corruption-free Public Service, a state government with ministers presided over by an Executive Prime Minister and, for a decade, West Cameroon provided the Vice Presidency for the Federal Republic of Cameroon. In what may be accurately described as Prof Anthony Ndi's seminal work, he contends and rightly so that solutions to the legion of problems that plague contemporary Cameroon may be easily found in the pages of The Golden Age of Southern Cameroons. Agents for this transformation do not have to be invented or imported from Mars; all we need is a patriotic spirit, political will, readiness to dialogue, transparency and commitment to democracy.